Redesign Mesin Guna Meningkatkan Produktivitas Menggunakan Metode Zero-One - Happy Lailatul Fitriana; Ilfan Feriantono; Sofriyah Izzatul Laily; Ribangun Bamban Jakaria (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In a company increasing productivity is very important. This increase can be done by improving technological innovation. The technology that was redesigned was the roaster machine. The aim of this research is to make machine use and maintenance easier with new designs that may be more user-friendly and more sophisticated control technology or more durable materials that can improve machine performance and longevity. The method used in this research is the Zero One method. The Zero-One method is a decision development method that aims to determine alternatives (criteria). The results of the analysis from this research are to create a machine that can be made in accordance with ergonomic standards for workers, thereby reducing downtime and reducing production cycle times, thereby allowing for increased output without increasing working hours.